A Cohort Study to Evaluate the Effect of Nutritional Intervention on Severe Acute Malnutrition Children Admitted to A Nutritional Rehabilitation Centre in A Tertiary Care Hospital in Central Gujarat, India - Panchal, Foram; Parmar, Rahul; Shringarpure, Kalpita; Damor, Jivraj (National journal of community medicine, 2024)
Background: Undernutrition is one of the most concerning health and development issues in India as well as in the world. Nutritional rehabilitation centres (NRC) were started by Government of India to control severe acute malnutrition. The aim is to assess the effect of nutrition interventional measures for severe acute malnutrition (SAM) children admitted at NRC through selected anthropometric indicators. Methodology: A hospital-based prospective cohort study was conducted at NRC of SSG Hospital, Vadodara, Gujarat from April to September 2022, all children of 6-60 months of age admitted during this period were observed during their stay with three follow-ups after discharge at 15 days interval. The data was entered in Microsoft Excel and was analysed using Medcalc Software. Results: A total of 76 children were analysed for anthropometric indicators. A statistically significant difference was obtained between the weight of children at admission, discharge and 3 follow-ups (ANOVA=141, p<0.001); difference of mid upper arm circumference (MUAC) (ANOVA=84.2, p<0.001) and difference of height (ANOVA=43.3. p<0.001) at admission, discharge and follow-up were also statistically significant. Conclusions: NRCs have had a positive impact on the selected anthropometric indicators of severe malnourished children but lag behind proper follow-up visits.